(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the health issues school-age girls in the Meerut district face when they menstruate. The primary goal of the research is to use factor analysis to determine and evaluate the health factors and preventative actions that have the greatest influence during menstruation. A random selection of 1500 responders was made from high schools spread across several talukas in the Meerut district. In this study, eighteen factors were taken into account. Using the SPSS software, factor analysis was used to identify the most important health and precautionary aspects.